Capturing the Essence: Employment of Dynamic Equivalence in Lakshmi Holmström’s Translation of Salma’s இரண ்டாம் ஜாமங்களின் கதை Iraṇṭām jāmaṅkaḷiṉ katai into English (International Journal of Food and Nutritional Sciences, 2022)
Translation is a nuanced art. It involves transferring not only words but also the cultural context from one language to another. In translating Salma’s இரண்டாம் ஜாமங்களின் கதை Iraṇṭām jāmaṅkaḷiṉ katai as The Hour Past Midnight, Lakshmi Holmström has used dynamic equivalence. Thus she makes sure that the translated text resonates with the target readers. At the same time, she preserves the essence of the original text. This paper deals with how Lakshmi Holmström has made use of dynamic equivalence in her translation through some illustrative examples.